2019
DOI: 10.4142/jvs.2019.20.e42
|View full text |Cite
|
Sign up to set email alerts
|

New foot-and-mouth disease vaccine, O JC-R, induce complete protection to pigs against SEA topotype viruses occurred in South Korea, 2014–2015

Abstract: Foot-and-mouth disease (FMD) is an acute epidemic that spreads rapidly among cattle and pigs. In 2014, in Korea, despite enforced vaccination, the type O Southeast Asia (SEA) topotype viruses (Mya-98 lineage) infected mainly cattle and pigs simultaneously, thereby causing enormous damage. If a vaccine that is completely protective against this FMD virus is developed and used, it can become a very important preventive measure in Asia, which is where this type of virus mainly circulates. The SEA topotype has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Among the seven serotypes of FMDV, serotypes O and SAT are, in particular, more unstable [ 19 ]. O JC, which belongs to the SEA topotype viruses (Mya-98 lineage) [ 20 ], appears to be the most unstable serotype O strain that we have previously dealt with. The O JC strain completely dissociated into 12S subunits by mild heating at 45 °C for 30 min, while other tested strains, including another serotype O virus, maintained over 80% of the initial content under the same conditions ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the seven serotypes of FMDV, serotypes O and SAT are, in particular, more unstable [ 19 ]. O JC, which belongs to the SEA topotype viruses (Mya-98 lineage) [ 20 ], appears to be the most unstable serotype O strain that we have previously dealt with. The O JC strain completely dissociated into 12S subunits by mild heating at 45 °C for 30 min, while other tested strains, including another serotype O virus, maintained over 80% of the initial content under the same conditions ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, FMD was prevalent until 2016, and another large-scale FMD outbreak occurred in 2014–2015 ( 9 14 ) which prompted the introduction of diverse serotype O vaccine strains besides O1 Manisa. In 2017, a comprehensive biannual vaccination program for cattle and goats and post-vaccination sero-monitoring, in addition to year-round serosurveillance, were launched ( 10 , 11 , 15 ). The current vaccination regimen was adopted after the serotype A FMD outbreak in porcine in the spring of 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it appears that the existing v / s are broadly cross-reactive and can provide protection against the circulating topotypes, except Cathay viruses, as demonstrated previously using O 1 /Campos v / s [ 24 , 25 ]. Several studies, mainly from South Korea, have reported the suitability of new putative strains for use in both pigs and cattle in their control programs [ 13 , 14 , 26 ].…”
Section: Resultsmentioning
confidence: 99%